Rabīndranātha o loka-sāhitya - Bhattacharya, Asutosh, 1909- (Kalikātā Biśvabidyālaẏa Rabīndranātha Ṭhākura baktrtāmālā, 1973)
Study on the influence of Bengali folklore and literature on the works of the Indian poet Rabindranath Tagore, 1861-1941.